Case Report: Gastric intramural hematoma with acute upper gastrointestinal bleeding in a child - Xiao, Ming; Lu, Jin; Chen, Yu; Sun, Weiwei; Sun, Youcheng; Li, Yutian; Jiang, Yang; Lian, Xingchen; Zhou, Zhengqiang; Qi, Xin (Frontiers in Pediatrics, 2025)
Gastric hematoma is an exceptionally rare condition in pediatric patients. It is characterized by the accumulation of blood within the gastric wall, resulting in the formation of a mass. Coagulopathy is the most common cause of gastric hematoma, although other etiologies include gastric ulcer, amyloidosis, pancreatitis, and splanchnic vascular aneurysms. However, the pathophysiology of gastric hematoma remains incompletely understood. It is presumed to be caused by ruptures of the submucosal vessels, leading to dissection of the muscular layer and the formation of a false lumen. Herein, we report the case of a 4 year-old girl who was admitted to our hospital with a large intragastric mass. She presented with hematemesis, and a large hematoma was visualized via gastroscopy. After treatment, the patient underwent a second follow-up gastroscopy, which showed that the gastric mass had subsided, and multiple gastric ulcers were found in the gastric wall. After excluding other causes, we considered that the gastric hematoma may have been caused by the ulcers. By discussing the clinical presentation and treatment options in this case, we hope to improve the understanding of pediatric gastric hematoma so that serious complications can be avoided in future cases.